Comparison of the Mitochondrial Genomes and Steady State Transcriptomes of Two Strains of the Trypanosomatid Parasite, Leishmania tarentolae. - Larry Simpson; Stephen M Douglass; James A Lake; Matteo Pellegrini; Feng Li (Public Library of Science (PLoS), 2015)
U-insertion/deletion RNA editing is a post-transcriptional mitochondrial RNA modification phenomenon required for viability of trypanosomatid parasites. Small guide RNAs encoded mainly by the thousands of catenated minicircles contain the information for this editing. We analyzed by NGS technology the mitochondrial genomes and transcriptomes of two strains, the old lab UC strain and the recently isolated LEM125 strain. PacBio sequencing provided complete minicircle sequences which avoided the assembly problem of short reads caused by the conserved regions. Minicircles were identified by a characteristic size, the presence of three short conserved sequences, a region of inherently bent DNA and the presence of single gRNA genes at a fairly defined location. The LEM125 strain contained over 114 minicircles encoding different gRNAs and the UC strain only ~24 minicircles. Some LEM125 minicircles contained no identifiable gRNAs. Approximate copy numbers of the different minicircle classes in the network were determined by the number of PacBio CCS reads that assembled to each class. Mitochondrial RNA libraries from both strains were mapped against the minicircle and maxicircle sequences. Small RNA reads mapped to the putative gRNA genes but also to multiple regions outside the genes on both strands and large RNA reads mapped in many cases over almost the entire minicircle on both strands. These data suggest that minicircle transcription is complete and bidirectional, with 3' processing yielding the mature gRNAs. Steady state RNAs in varying abundances are derived from all maxicircle genes, including portions of the repetitive divergent region. The relative extents of editing in both strains correlated with the presence of a cascade of cognate gRNAs. These data should provide the foundation for a deeper understanding of this dynamic genetic system as well as the evolutionary variation of editing in different strains.